Migration and Economic Mobility in Tanzania : Evidence from a Tracking Survey - Beegle, Kathleen; De Weerdt, Joachim; Dercon, Stefan (MIT Press, 2012)
This study explores to what extent migration has contributed to improved living standards of individuals in Tanzania. Using a thirteen-year panel survey, we find that migration between 1991 and 2004 added 36 percentage points to consumption growth. Although moving out of agriculture resulted in much higher growth than staying in agriculture, growth was always greater in any sector if the individual physically moved. As to why more people do not move given the high returns to geographical mobility, analysis finds evidence consistent with models in which exit barriers set by home communities prevent the migration of some categories of people.